Efficacy and safety of Shenkang injection as adjuvant therapy in patients with diabetic nephropathy: A protocol for systematic review and meta-analysis - Wang, Yanping (Medicine (Baltimore), 2020)
BACKGROUND: Diabetic nephropathy is a frequent microvascular complication of diabetes mellitus that causes end-stage renal disease most of the time. In China, Shenkang injection is one of widely used traditional Chinese medicine for treating chronic kidney disease, but its efficacy and safety have not yet been clarified. We will systematically review the current randomized controlled trial (RCT) evidence to summarize the efficacy and safety of Shenkang injection in treating diabetic nephropathy. METHODS: We will search 7 literature databases including PubMed, EMBASE, Cochrane Library, Sinomed, Chinese National Knowledge Infrastructure, Wanfang, and VIP. Two trial registry platforms will also be searched. The time frame of the search will be from the inceptions of the databases to December 31, 2020. RCTs assessing Shenkang injection combined with basic treatments versus basic treatments alone for treating diabetic nephropathy will be included. The risk of bias within the individual RCTs will be evaluated using criteria proposed by the Cochrane Handbook 5.1.0. The primary outcomes to be investigated are glomerular filtration rate and serum creatinine; the secondary outcome will include 24-hour urine albumin excretion rate, blood urea nitrogen, fasting blood glucose, postprandial blood glucose, hemoglobin A1c, total cholesterol, triglyceride, response to treatment, and incidence of adverse events. The effect data of individual RCTs by performing random-effects model meta-analysis. Statistical heterogeneity will be measured by the Cochran Q test and I-squared statistics. Three subgroup analyses, set based on clinical experience, will be performed to explore the sources of heterogeneity. Sensitivity analyses excluding RCTs with high risk of bias and using fixed effect model will be done to test the robustness of the meta-analytic results. Publication bias across included RCTs will be evaluated by funnel plots and Egger test. RESULTS: This study will provide systematic review on the efficacy and safety of Shenkang Injection as adjuvant therapy in patients with diabetic nephropathy by rigorous quality assessment and reasonable data synthesis. The results will be submitted to a peer-reviewed journal for publication. CONCLUSION: This systematic review will provide the best evidence currently on Shenkang Injection as adjuvant therapy in patients with diabetic nephropathy. INPLASY REGISTRATION NUMBER: INPLASY2020110014.